A flexible air separation process: 1. Design and steady‐state optimizations. Issue 11 (17th July 2019) - Caspari, Adrian; Offermanns, Christoph; Schäfer, Pascal; Mhamdi, Adel; Mitsos, Alexander
Abstract: The flexible operation of energy‐intensive processes, such as cryogenic air separation, has economic potential due to increasing fluctuations of the electricity markets. Multiproduct air separation processes with high ratios of liquid product are very promising for flexible operation due to storable products. We present a process design with an integrated liquefication cycle and liquid assist operation, that facilitates a high liquid product ratio and a flexible process operation. We use a mechanistic dynamic process model in steady‐state process optimizations covering the wide operational range of the proposed process. The optimization results show that the power demand can be varied in a range from 3.5 to 28 MW without violating operational constraints by changing the nitrogen and oxygen production rates. Thus, the proposed process is a promising air separation candidate for flexible operation with respect to fluctuating electricity markets.